Subacute thyroiditis after SARS-CoV2 vaccines- a systematic review - Magdalena Grześk; Daniel Rogowicz; Magdalena Ostrowska; Dominika Skwara; Paweł Denisiuk; Szymon Kaczyński (Polish Pharmaceutical Society, 2022)
During the pandemic of Coronavirus disease, many procedures and restrictions were implemented to stop the spread of the virus, though none of which is as efficient as vaccination. COVID-19 vaccines are vital for returning to time before the pandemic. Moreover, analyzing the protective effects and complications of vaccines it is crucial to minimize its adverse effects. Our review analyzed 28 cases described in medical journals, of patients who developed subacute thyroiditis (SAT) after COVID-19 vaccines. Most commonly, SAT follows upper respiratory tract infections. Until 2016 only 5 cases of SAT after vaccinations had been reported. After COVID-19 vaccines, SAT developed mostly among women. The most cases were observed after the first dose, after seven days on average. In all presented patients, symptoms were similar, including mostly hyperthyroidism signs and pain. TSH level among 82% was low or undetectable. Treatment in most cases included anti-inflammatory and analgesics medications, propranololi hydrochloridum, and glucocorticoids, leading to full recovery. SAT occurs in healthy individuals with negative infection and thyroid disease medical history as well as in patients associated with thyroid diseases. The mechanism, which may lead to subacute thyroiditis, may be complex and involve Angiotensin converting enzyme 2 (ACE2) receptors, cross-reactions between thyroid peroxidase and spike protein, and the autoimmune/inflammatory syndrome induced by adjuvants (ASIA). Cross-reaction between thyroid peroxidase and spike protein, nucleoproteins, and membrane protein of SARS-CoV-2 was proved on animal models. SARS-CoV2 infection mechanism requires the presence of ACE2 receptors and transmembrane serine protease (TMPRSS2), which were both found in thyroid follicular cells. Spike protein, produced after vaccination, is modified (HexaPro), and it is more stable and binds higher. Some authors suggest that in effect it may lead to pyroptosis and thyroid cells destruction. Another mechanism of post-vaccine SAT is ASIA, which manifests with various symptoms, and although it is undermined by many health professionals some authors diagnosed ASIA in patients with SAT. SAT is a self-limiting disease and non-life threatening. However, very important is the diagnosis, especially in individuals with risk factors of cardiovascular disease to prevent side effects of hyperthyroidism like cardiac arrhythmias, tachycardia, coronary syndromes and side effects from other organs.